Psychosocial impact on puberphonic and effectiveness of voice therapy: A case report - Bhattarai, B; Shrestha, A; Shah, Sunil Kumar (Journal of College of Medical Sciences-Nepal, 2010)
Puberphonia is a rare disorder, in which the patient manifests higher register voice than others of their same age group. Manifestation is less in women than men. The prevalence is 1 in 900,000. Apart from impact on voice of patient, puberphonia also has impact on the psycho-social aspect. Different treatment modalities have been put forward in the past, many of which lack validity and EBP. Voice therapy has proven to be the most effective in the management of puberphonia. Voice Handicap Index (VHI) is a tool for assessing the perceived handicap by the patient. VHI has 3 parts and overall score of 120 and individual subset has score of 40 each. Result: Patient who received voice therapy obtained better score on the overall scale as well as on each subsets of the VHI. Conclusion: The study concludes that the voice therapy not only improves the voice quality of the patient, but also improves the quality of life of the patient. The impact of voice disorder (puberphonia) is most prominent on the emotional section. Keywords: Puberphonia; voice therapy; VHI. DOI: 10.3126/jcmsn.v6i1.3605 Journal of College of Medical Sciences-Nepal, 2010, Vol. 6, No. 1, 57-62